Racial disparities in COVID-19 mortality across Michigan, United States. (March 2021) - Parpia, Alyssa S.; Martinez, Isabel; El-Sayed, Abdulrahman M.; Wells, Chad R.; Myers, Lindsey; Duncan, Jeffrey; Collins, Jim; Fitzpatrick, Meagan C.; Galvani, Alison P.; Pandey, Abhishek
Abstract: Background: Black populations in the United States are being disproportionately affected by the COVID-19 pandemic, but the increased mortality burden after accounting for health and other demographic characteristics is not well understood. We examined characteristics of individuals who died from COVID-19 in Michigan by race stratified by their age, sex and comorbidity prevalence to illustrate and understand this disparity in mortality risk. Methods: We evaluate COVID-19 mortality in Michigan by demographic and health characteristics, using individual-level linked death certificate and surveillance data collected by the Michigan Department of Health and Human Services from March 16 to October 26, 2020. We identified differences in demographics and comorbidity prevalence across race among individuals who died from COVID-19 and calculated mortality rates by age, sex, race, and number of comorbidities. Findings: Among the 6, 065 COVID-19 related deaths in Michigan, Black individuals are experiencing 3·6 times the mortality rate of White individuals ( p <0.001), with a mortality rate for Black individuals under 65 years without comorbidities that is 12·6 times that of their White counterparts ( p <0.001). After accounting for age, race, sex, and number of comorbidities, we find that Black individuals in all strata are at higher risk of COVID-19 mortality than their White counterparts. Interpretation: Our findings demonstrate that Black populations are disproportionately burdened by COVID-19 mortality, even after accounting for demographic and underlying health characteristics. We highlight how disparities across race, which result from systemic racism, are compounded in crises. Funding: ASP, AP and APG were funded by NSF Expeditions grant 1918784, NIH grant 1R01AI151176-01, NSF Rapid Response Research for COVID-19 grant RAPID-2027755, and the Notsew Orm Sands Foundation. MCF was supported by NIH grant K01AI141576.